Answers

2014-09-17T16:17:02+05:30
tan(75) = tan(30+45) \\ tan(30+45)= \frac{tan30+tan45}{1-tan30.tan45}  \\ = \frac{( \frac{1}{ \sqrt{3} }+1) }{1- \frac{1}{ \sqrt{3} }.1 }  \\ = \frac{ \frac{1+ \sqrt{3} }{ \sqrt{3} } }{ \frac{ \sqrt{3} -1}{ \sqrt{3} } } \\tan75 = \frac{ \sqrt{3}+1 }{ \sqrt{3}-1 }
Now, Tan(90)= tan(45+45)
tan(45+45) =  \frac{tan45+tan45}{1-tan45.tan45}  \\ = \frac{1+1}{1-1*1} = \frac{1}{0} 
= infinity

7 3 7
2014-09-17T16:47:00+05:30
Tan(75)=Tan(30+45)=Tan30+Tan45/1-Tan30×Tan45=1/√3+1/1-1/√3×1
2 4 2